2016
DOI: 10.1016/j.resmic.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic acid in plant–pathogen interactions: a key molecule for in planta bacterial virulence and fitness

Abstract: The plant pathogenic bacterium Pseudomonas savastanoi, the causal agent of olive and oleander knot disease, uses the so-called "indole-3-acetamide pathway" to convert tryptophan to indole-3-acetic acid (IAA) via a two-step pathway catalyzed by enzymes encoded by the genes in the iaaM/iaaH operon. Moreover, pathovar nerii of P. savastanoi is able to conjugate IAA to lysine to generate the less biologically active compound IAA-Lys via the enzyme IAA-lysine synthase encoded by the iaaL gene. Interestingly, iaaL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 76 publications
4
43
0
Order By: Relevance
“…A Psn PB213 iaaL mutant obtained by Tn 5 transposition displayed virulence attenuation in woody oleander plants in comparison with the wild-type strain (Glass and Kosuge, 1988). Conversely, a recent report showed that a knockout mutation of the iaaL gene in a different Psn isolate, Psn23, yielded a hypervirulent strain that resulted in a severe increase in knot size, higher systemic dispersion and a larger final population size than the wild-type strain in micropropagated (i.e., non-woody) oleander plants (Cerboneschi et al, 2016). Further studies are necessary to clarify the role of the iaaL gene in the virulence of P. savastanoi strains isolated from different hosts.…”
Section: Pathogen-produced Phytohormones and Their Role In Diseasementioning
confidence: 99%
“…A Psn PB213 iaaL mutant obtained by Tn 5 transposition displayed virulence attenuation in woody oleander plants in comparison with the wild-type strain (Glass and Kosuge, 1988). Conversely, a recent report showed that a knockout mutation of the iaaL gene in a different Psn isolate, Psn23, yielded a hypervirulent strain that resulted in a severe increase in knot size, higher systemic dispersion and a larger final population size than the wild-type strain in micropropagated (i.e., non-woody) oleander plants (Cerboneschi et al, 2016). Further studies are necessary to clarify the role of the iaaL gene in the virulence of P. savastanoi strains isolated from different hosts.…”
Section: Pathogen-produced Phytohormones and Their Role In Diseasementioning
confidence: 99%
“…Plant pathogens have been demonstrated to produce IAA to hijack plant immunity, by subverting plant auxin signaling to increase host susceptibility to infection [6,[12][13][14]. In addition, microbial IAA is also essential as signal molecules within the producer populations, and in plant pathogenic bacteria, IAA was demonstrated to affect the expression of genes of their virulence network [7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…nerii regulates free IAA levels in the infected tissues by its conversion to the conjugate IAA-Lysine (hereafter indicated as IAA-Lys), supposed to be less biologically active than the IAA free form. This reaction is mediated by the enzyme IAA-Lys synthase, encoded by the iaaL gene [17]. Interestingly, most of the P. syringae pathovars and strains possess the iaaL gene in their genomes, even if they do not cause hyperplastic symptoms, and this gene appears to be very well conserved and present independently from the genes for IAA biosynthesis [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations